2017
DOI: 10.1055/s-0037-1606014
|View full text |Cite
|
Sign up to set email alerts
|

Association of psychotropic drug use with falls among older adults in Germany. Results of the German Health Interview and Examination Survey for Adults 2008 – 2011 (DEGS1)

Abstract: PurposeTo investigate the association of psychotropic drug use with falls among older adults in Germany based on data from the National Health Interview and Examination Survey for Adults -2011. MethodsDEGS1 collected data on drug use in the past 7 days and on falls occurred in the last 12 months. Study participants were older adults aged 65-79 years with complete data on drug use and falls (N = 1,833). Odds ratio (OR) and 95% confidence intervals (95% CI) were derived from logistic regression models adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
(57 reference statements)
2
4
0
Order By: Relevance
“…The use of psychoactive medicines would increase 1.79 times of the risk of falls higher than patients who did not use (95% CI 1.10-2.90). These results were consistent to previous studies (Bloch et al, 2011;Du et al, 2017;Mustafidah, 2019). A Study conducted in Germany elderly population in 2008-201 revealed that psychoactive drug use was associated with falls in the elderly with OR 1.64 (95% CI 1.14-2.37) (Du et al, 2017).…”
Section: Association Psychoactive Drugs Use and Fall Risksupporting
confidence: 94%
See 2 more Smart Citations
“…The use of psychoactive medicines would increase 1.79 times of the risk of falls higher than patients who did not use (95% CI 1.10-2.90). These results were consistent to previous studies (Bloch et al, 2011;Du et al, 2017;Mustafidah, 2019). A Study conducted in Germany elderly population in 2008-201 revealed that psychoactive drug use was associated with falls in the elderly with OR 1.64 (95% CI 1.14-2.37) (Du et al, 2017).…”
Section: Association Psychoactive Drugs Use and Fall Risksupporting
confidence: 94%
“…The use of psychoactive medicines in the case group was statistically and significantly higher than that in the control group (31.16% vs 21.38%, p<0.05) (Table III). This is consistent with the finding of the previous study in Germany revealing that the elderly with fall had higher psychoactive drugs use (33.1% vs. 20.7%) (Du et al, 2017). The characteristics of psychoactive medicines evaluated in the study were duration of drug use, the number of psychoactive drugs, and The Standardized Daily Dose (SDD).…”
Section: Volume 30 Issue 3 (2019)supporting
confidence: 91%
See 1 more Smart Citation
“…A retrospective cohort study of 73690 community-dwelling veterans found that patient on one or more psychoactive drug or increased dosage of that were observed to have a significantly increased fall risk [12]. Using data of German Health Interview and Examination Survey for Adults 2008-2011, an epidemiological study found that self-reported psy- choactive drugs were overall associated with 64% increase in the risk of falls and recurrent falls on self-report in the past 12 months in community-dwelling older adults aged 65-79 years [10]. A prospective cohort of 1759 community-dwelling healthy older adults followed up for 12 months by telephone showed a 90% higher fall risk among psychoactive drug users [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are many studies about the relationships between psychoactive drug use and falls in community-dwelling older people [6][7][8][9][10][11][12][13]; however, this relationship has not been examined enough in outpatients in Turkey. Older outpatients with severe health problems, multi-morbidities, and complicated diseases are at high risk of fall.…”
mentioning
confidence: 99%